Thor : the mighty avenger. Vol. 2 - Langridge, Roger (Marvel Worldwide, Inc., 2011)
Thor is making the best of his banishment from Asgard by befriending the mortal Jane and taking her on a tour of the wonders of Earth, but the moment is ruined when Thor clashes with Namor, the Sub-Mariner.